GLP-1 Receptor Agonists for Type 2 Diabetes: Weight Loss and Beyond—A Systematic Review - Dr Mohd Fazal Ahmed Makki; Dr. Ankur Singh; Dr Pushkar Mani (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have revolutionized the management of type 2 diabetes mellitus (T2DM) by reducing glucose levels by decreasing glucose-stimulated insulin release, glucagon inhibition, gastric emptying delay and by inducing satiety. Besides their effects on glycaemia, their beneficial effects on weight and cardiometabolic risk have placed this class at the centre of current guidelines. Methods: We undertook a structured narrative review of randomised controlled trials (RCTs), meta-analyses, and key mechanistic studies evaluating liraglutide, exenatide, and related GLP-1 RAs in adults with T2DM. Sources included pivotal LEAD trials, comparative studies versus insulin glargine or oral agents, and analyses of safety signals (gastrointestinal events, hypoglycaemia, and heart-rate effects). We also reviewed mechanistic work on adipose-tissue and extracellular-matrix (ECM) remodelling and emerging cardiometabolic indications Results: Across RCTs, GLP-1 RAs consistently reduce HbA1c by 0.8–1.5% versus baseline and achieve clinically meaningful weight loss (approx. 2–5.5 kg vs active comparators), with low intrinsic hypoglycaemia risk when not combined with sulfonylureas/insulin. Liraglutide added to sulfonylurea therapy improves glycaemic control and weight relative to rosiglitazone or placebo; versus insulin glargine, liraglutide yields greater HbA1c reduction with weight loss rather than weight gain. Meta-analytic data show modest reductions in body weight and blood pressure alongside a small mean increase in heart rate ( 1–2 bpm). Mechanistic studies indicate favourable adipose-tissue biology (e.g., increased adiponectin; ECM effects) with exendin-4/GLP-1 signalling, plausibly contributing to insulin sensitivity and weight outcomes. Trials in specialised populations (e.g., younger adults) and related metabolic indications (NAFLD/NASH, obesity) are expanding the therapeutic scope. Conclusion: GLP-1 RAs deliver robust, durable HbA1c lowering, clinically relevant weight loss, and broader cardiometabolic benefits with a generally manageable safety profile. Gastrointestinal adverse events are the most frequent and usually attenuate over time; heart-rate increases are small and of uncertain clinical relevance. Evidence supports GLP-1 RAs as foundational agents for many adults with T2DM, especially when weight reduction is desirable. Future work should refine patient selection, long-term cardiometabolic outcomes, and multimodal strategies (e.g., combination incretin therapy).